United States, arctic fuel station at Anchorage harbor - Sorensen, Clarence Woodrow, 1907-1982; Harris, Eugene V., 1913-1978 (1934)
Looking over snow bank on side of road to Arctic Fuel shop. Grayscale Sorensen Safety Negatives, Binder: North & Central America 3